Evaluation of the Relationship between Age and Outcome after Microvascular Reconstruction among Patients with Recurrent Head and Neck Squamous Cell Carcinoma - Patel, Viraj M.; Stern, Carrie; Miglani, Amar; Weichman, Katie E.; Lin, Juan; Ow, Thomas J.; Garfein, Evan S. (Journal of Reconstructive Microsurgery, 2017)
Background In patients with head and neck squamous cell carcinoma (HNSCC), disease recurrence remains a significant obstacle to long-term survival. If possible, surgical salvage with reconstruction remains the best treatment option for patients with recurrence. Currently, there is no literature discussing whether age should preclude microvascular reconstruction in these patients. We hypothesize that older age alone does not affect outcomes.Methods A retrospective chart review of patients with HNSCC at our institution between 2008 and 2015 was performed. Patients were included if they underwent simultaneous resection and flap reconstruction for recurrent HNSCC. Data collected included age, sex, primary site, type of reconstruction, previous treatments, postoperative complications (systemic and reconstructive), and overall survival.Results A total of 65 patients met inclusion criteria for the review: 42 (64.6%) patients ≤70 years and 23 (35.4%) patients > 70 years. Overall survival was not significantly different between the younger and older groups (p = 0.199). Five-year survival was 60.1% in the younger group and 46.8% in the older group. No significant difference was found in reconstructive complication rates (p = 0.179) or systemic complication rates (p = 0.241) between the two groups. Multivariate logistic regression analysis further showed no significant association between patients' age (≤70 years or > 70 years) and reconstructive complications (p = 0.396) or systemic complications (p = 0.119).Conclusion Age is not significantly associated with complications among patients undergoing resection and reconstruction for recurrent HNSCC. Microvascular reconstruction remains a feasible option in older patients with recurrent HNSCC. Advanced age alone should not preclude the surgical management of recurrent HNSCC.
Keywords: head and neck cancer; squamous cell carcinoma of the head and neck; free tissue flaps; microsurgical free flaps; reconstructive surgical procedures; palliative surgery; life expectancy